Examining Green Transformational Leadership, Group Cohesiveness and Organizational Justice in Reducing Turnover Intention and Enhancing Sustainable Employee Performance - Septiani, Lisa; Herminingsih, Anik (DINASTI RESEARCH, 2025)
This research investigates how green transformational leadership (GTL), group cohesiveness (GC), and organizational justice (OJ) affect employee sustainable performance (ESP), with turnover intention (TOI) acting as an intermediary. The study, conducted at PT Puyo Indonesia Kreasi, emphasizes the significance of sustainable leadership, teamwork, and fairness in boosting employee performance that aligns with environmental, social, and economic objectives. Utilizing Structural Equation Modeling (SEM), the results indicate notable positive correlations between green transformational leadership, group cohesiveness, organizational justice, and employee sustainable performance, while turnover intention negatively mediates these connections. The study emphasizes an integrated approach that combines eco-friendly leadership, cohesive teamwork, and justice driven policies to enhance ESP and minimize TOI. GTL fosters an environmentally conscious workplace by embedding sustainability values into corporate culture, inspiring employees toward sustainable behaviors. GC strengthens collaboration, trust, and shared commitment, creating a foundation for long-term performance. OJ enhances employee motivation and loyalty by ensuring fairness in decision-making and resource allocation. However, high TOI disrupts ESP by reducing engagement and workforce stability. The findings offer managerial insights, advocating for sustainability focused leadership programs, structured team building, and fairness audits. Future research should explore these relationships across diverse contexts using longitudinal methods to capture dynamic changes in sustainable performance.